The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/catal11020197
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Modified Nano Mordenite for Carbonylation of Dimethyl Ether

Abstract: Mordenite (H-MOR) catalysts were synthesized by a hydrothermal method, and silver-modified mordenite (Ag-MOR) catalysts were prepared by ion exchange with AgNO3 at different concentrations. The performance of these catalysts in the carbonylation of dimethyl ether (DME) to methyl acetate (MA) was also evaluated. The catalysts were characterized by Ar adsorption/desorption, XRD, ICP-AES, SEM, HRTEM, 27Al NMR, H2-TPR, NH3-TPD, Py-IR, and CO-TPD. According to the characterization results, Ag ion exchange sites wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…To further investigate the interaction of H 3 PO 4 with Ag NPs, we characterized Ag + /MCM-48 (unreduced) and Ag + / MCM-48-H 3 PO 4 (unreduced) by H 2 -TPR (Figure 4f). The TPR profile of Ag + /MCM-48 (unreduced) demonstrates reduction in peak maxima at temperatures close to 80 and 280 °C, attributed to the reduction of Ag x O y and some positive valence silver in MCM-48 pores, 9,36 respectively. The addition of H 3 PO 4 leads to the shift of TPR peak to the higher temperature up to 155 °C, indicated that there may be a strong coordination between the loaded phosphoric acid and Ag ions, and it is consistent with the XPS and 31 P SSNMR results above.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the interaction of H 3 PO 4 with Ag NPs, we characterized Ag + /MCM-48 (unreduced) and Ag + / MCM-48-H 3 PO 4 (unreduced) by H 2 -TPR (Figure 4f). The TPR profile of Ag + /MCM-48 (unreduced) demonstrates reduction in peak maxima at temperatures close to 80 and 280 °C, attributed to the reduction of Ag x O y and some positive valence silver in MCM-48 pores, 9,36 respectively. The addition of H 3 PO 4 leads to the shift of TPR peak to the higher temperature up to 155 °C, indicated that there may be a strong coordination between the loaded phosphoric acid and Ag ions, and it is consistent with the XPS and 31 P SSNMR results above.…”
Section: Resultsmentioning
confidence: 99%
“…In heterogeneous catalysis using supported zeolite catalysts, active site concentration, feed diffusion, and site accessibility play vital roles . Incorporation of metallic nanoparticles onto the channels and cavities of zeolite materials has a critical effect on their catalytic properties and stability. Inoue et al reported in 1995 the effect of silver-exchanged zeolites on the methanol to aromatics conversion .…”
Section: Introductionmentioning
confidence: 99%
“…Various metallic species, such as ions, clusters and nanoparticles, deposited on the surface or implanted into zeolites and other microporous, mesoporous and nanoporous matrices, are of great interest for the development of nanostructured materials for diverse applications in areas such as catalysis [1][2][3][4][5][6][7], water purification [8][9][10][11][12], general medicine [13,14], synthesis of antimicrobial and antifungal materials [15][16][17] and in a number of otherareas [18][19][20][21][22][23]. The development of packing materials containing zeolites modified with silver, copper and zinc ions and metal nanoparticles, which have antimicrobial and fungicidal properties is reviewed in [15,20,23].…”
Section: Introductionmentioning
confidence: 99%